ANALYSIS OF VALUE FOR MONEY ON THE FINANCIAL PERFORMANCE OF THE REGIONAL DEVELOPMENT PLANNING AGENCY REGIONAL DEVELOPMENT (BAPPEDA) ROKAN HULU REGENCY - Silvitri, Egilia; Ripira, Risti; Annisa, Nona; Basri, Yesi Mutia (Institut Pendidikan Tapanuli Selatan, 2025)
This research was conducted with the aim of measuring the financial performance of the Regional Development Planning Agency (Bappeda) of Rokan Hulu Regency in 2020 and 2021 using the value for money measurement method. The value for money measurements used are economy, efficiency, and effectiveness with data taken from the Government Agency Performance Report (LKjIP) of the Regional Development Planning Agency (Bappeda) of Rokan Hulu Regency in 2020 and 2021. The research design used is qualitative research using primary and secondary data. The data collection techniques used in this study used interviews and documentation methods. The results of this study indicate that the financial performance of the Regional Development Planning Agency (Bappeda) of Rokan Hulu Regency in 2020 is included in the economic, inefficient and ineffective categories. Meanwhile, in 2021 it is included in the economic, inefficient and ineffective categories. The cause of measuring value for money is inefficient and ineffective because there are several activities in the program that do not meet the predetermined targets.